Cervical Ectopic Pregnancy after IVF: A Case Report of Successful Conservative Management with Transvaginal Amniotic Sac Aspiration and Intra saccular Methotrexate Injection - Surur, Feruz; Mutesim (Ethiopian Journal of Reproductive Health, 2022)
Cervical Ectopic Pregnancy (CEP) is a very rare condition accounting for less than 1 % of all Ectopic Pregnancies. Early diagnosis and management of the case are very essential in order to avoid serious and life-threatening complications, which are difficult to successfully manage in resource-poor settings. Here we are presenting a case report of a 38 yr. old Ethiopian mother who developed CEP following her 1st IVF therapy for secondary infertility secondary to Asherman’s syndrome. She was successfully managed conservatively, with aspiration and subsequent installation of methotrexate into the gestational sac. Early diagnosing with transvaginal ultrasound and serial B HCG measurement coupled with immediate therapeutic measures are the key issues in preventing the severe life-threatening complications of CEP and conserve the subsequent fertility potential of such patients.